2015
DOI: 10.2147/tcrm.s88878
|View full text |Cite
|
Sign up to set email alerts
|

Massive hemorrhage management – a best evidence topic report

Abstract: IntroductionMassive hemorrhage remains a major cause of potentially preventable deaths. Better control of bleeding could improve survival rates by 10%–20%. Transfusion intervention concepts have been formulated in order to minimize acute traumatic coagulopathy. These interventions still have not been standardized and vary among medical centers.Materials and MethodsBased on a literature search using free term keywords and Medical Subject Heading (MeSH) index, we analyzed published articles addressing massive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…According to the literature, these data are in accordance with those of other authors who found ROTEM to be effective in reducing FFP and PC consumption in a cardiac intensive care unit [14], during liver transplantation [15], and also in management of traumatic bleeding [16] and massive hemorrhage management [17]. This approach to coagulation assessment protects patients from unnecessary FFP and PC administration which are generally connected with increased morbidity and mortality.…”
Section: Discussionsupporting
confidence: 86%
“…According to the literature, these data are in accordance with those of other authors who found ROTEM to be effective in reducing FFP and PC consumption in a cardiac intensive care unit [14], during liver transplantation [15], and also in management of traumatic bleeding [16] and massive hemorrhage management [17]. This approach to coagulation assessment protects patients from unnecessary FFP and PC administration which are generally connected with increased morbidity and mortality.…”
Section: Discussionsupporting
confidence: 86%
“… 7 Following other authors’ recommendations, we followed a restrictive blood transfusion strategy. 19 The fibrinogen level <1.5 g/L during thrombolysis was not associated with an increased bleeding risk. 16 , 20 It is well documented that larger doses as well as increased duration of thrombolysis are associated with an increased risk of bleeding.…”
Section: Discussionmentioning
confidence: 89%
“…In the setting of acute uncontrollable haemorrhage, RBC transfusion frequently saves lives [ 16 ]. This common understanding is based on strong clinical experience, albeit on weak study evidence, because denying transfusions in a life-threatening condition for the sake of a trial would be undoubtedly unethical.…”
Section: Transfusion In Surgerymentioning
confidence: 99%